Nutritional Enhancement of Rice Noodles with Watermeal (Wolffia globosa) - Nidthaya Seephua; Yu Liu; Hua Li; Apichaya Bunyatratchata; Onanong Phuseerit; Sirithon Siriamornpun (Foods)
This study examined the impact of incorporating watermeal (Wolffia globosa) on the physicochemical characteristics, antioxidant activity, and starch and protein digestibility of rice noodles. The addition of watermeal powder (1, 3, 5%) significantly enhanced the nutritional and functional attributes of the noodles. The formulation with 5% watermeal (WF5) demonstrated a twofold increase in protein content compared to the control, along with a marked increase in the chlorophyll content as the watermeal concentration increased (p < 0.05). Moreover, fortifying the noodles with watermeal enhanced their bioactive compound content and antioxidant activity in all fortified noodles. Starch digestibility analyses revealed an increase in the resistant starch and slowly digestible starch, along with a reduction in the rapidly digestible starch and the estimated glycemic index. Protein digestibility in the WF5 sample improved by 22% compared to the control. These findings emphasize the capability of watermeal as a sustainable, plant-based ingredient for developing nutrient-rich noodle products with enhanced health benefits.